The trends and development of elections, civil liberties and democracy in the muslim world, 1998-2008 - Rohaizan Binti Baharuddin (2011)
The purpose of this study is to examine the practices of democracy, civil liberties and elections in 47 Muslim countries between the years 1998 to 2008. Specifically, in the Muslim world context, this study attempts to answer the following questions - how was the performance of civil liberties and elections; which variation of democracy was practiced most; how did the elections, civil liberties and democratic transitions take place and what patterns did they follow; and what is the best predictor of democracy – elections or civil liberties. Based on the data primarily collected from Freedom House, this study demonstrates the aggregate findings as follows - firstly, the 'not free not fair' elections, the 'limited' civil liberties and the 'Illiberal Partial Democracy' were the most dominant nature of elections, civil liberties and democracy practiced in the Muslim world; secondly, a sum of 413 Muslim regimes out of 470 remained the same as their democratic origin points, without any transitions to a better or worse levels of democracy, throughout these 11 years; thirdly, a slow, yet steady positive transition of both elections and civil liberties occurred in the Muslim world with changes in the nature of elections becoming much more progressive compared to the civil liberties' transitions; and lastly, with 66.67% occurrences, elections proved